Internet de las cosas en el ámbito de la atención médica: tendencias y desafíos. - Arango Astorga, Pedro; Garcia Garcia, Yadira (Revista Cubana de Informática Médica)
The internet of things has maintained continuous growth in recent years. The potentialities of use that it shows in different fields have been widely documented. Its effective use in the field of health can bring improvements in the efficiency of medical treatments, prevention of risky situations, help raising the quality of service and provide support for decision-making. The present review explores into core aspects of its use in order to analyze trends, challenges and strengths. Document analysis was used to show the main characteristics of these systems, as well as their architecture, tools used for the management of the captured data and security mechanisms. The use of the internet of things in the health field has a great impact, improving the lives of millions of people around the world and providing great opportunities for the development of intelligent health systems.